(untitled) (Journal of Dhaka Medical College, 2010)
Jejunogastric Intussusception is rare but potentially serious complication of gatrojejunostomy or gastrectomy requiring early diagnosis and prompt surgical intervention in acute form of the complication. Upper GI Endoscopy by a familiar person with this rare condition is diagnostic. The clinical picture of acute intestinal obstruction with haematemesis in the back ground of gastrectomy or gastrojejunostomy may make the illusive diagnosis definite and demand surgery to reduce morbidity and mortality of the patients. In our all the 4 cases Upper G I Endoscopy found to be diagnostic. Keywords: Jejunogastric Intussusception; Upper GI Endoscopy; Acute intestinal obstruction. DOI: 10.3329/jdmc.v17i2.6598 J Dhaka Med Coll. 2008; 17(2) : 134-137